Producing mands in concurrent operant environments. Issue 1 (20th June 2019) - Seaver, Jonathan P.; Bourret, Jason C.
Abstract : This study examined strategies designed to increase the rate of targeted, low‐probability mands in a concurrent operant environment. We examined the effects of schedule manipulations, prompt manipulations, motivating operation manipulations, and combined behavioral process manipulations. Increases in target mands were produced for all 8 participants. Schedule manipulations were effective in producing increased rates of targeted mands for 3 of 8 participants, whereas prompt manipulations were effective for 4 of 8 participants. Motivating operation manipulations were effective in producing increased rates of targeted mands for 2 of 8 participants and combined behavioral process manipulations were effective for the single participant exposed to the combination.